Morphological and phytochemical analysis of ocimum gratissimum linn. – A potential source of natural eugenol - PRANAB GIRI, (International Journal of Pharma and Bio Sciences, 2017)
This article deals with how different morphological, meteorological and edaphic parameters are correlated with the oil production in Ocimum gratissimum, the most potent eugenol producer among the available species of Ocimum growing naturally in the agro climatic conditions of West Bengal (India). This correlation has been established through extensive survey on this species growing in eight districts of West Bengal in respect of its various agro morphological traits. Emphasis should be given on some specific traits and parameters for cultivation of this species as discussed in this article with the view to produce more essential oil as well as eugenol in a cost effective manner.